2014
DOI: 10.1371/journal.pone.0099425
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Shock Protein 90 Promotes Nuclear Transport of Herpes Simplex Virus 1 Capsid Protein by Interacting with Acetylated Tubulin

Abstract: Although it is known that inhibitors of heat shock protein 90 (Hsp90) can inhibit herpes simplex virus type 1 (HSV-1) infection, the role of Hsp90 in HSV-1 entry and the antiviral mechanisms of Hsp90 inhibitors remain unclear. In this study, we found that Hsp90 inhibitors have potent antiviral activity against standard or drug-resistant HSV-1 strains and viral gene and protein synthesis are inhibited in an early phase. More detailed studies demonstrated that Hsp90 is upregulated by virus entry and it interacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 45 publications
0
47
0
Order By: Relevance
“…Just 30 min after infection, Kaposi's sarcoma-associated herpes virus enhances tubulin acetylation significantly [156]. About 4 h post infection, herpes simplex virus type 1 (HSV-1) increases tubulin acetylation, which in turn enhances HSP90 binding to microtubules and facilitates nuclear localization of viral capsid protein [157]. Notably, this effect is completely opposite from that on NF-AT nuclear localization [150], indicating that tubulin acetylation regulates nuclear import in a context-dependent manner.…”
Section: Tubulin Acetylation In Immune and Viral Responsesmentioning
confidence: 99%
“…Just 30 min after infection, Kaposi's sarcoma-associated herpes virus enhances tubulin acetylation significantly [156]. About 4 h post infection, herpes simplex virus type 1 (HSV-1) increases tubulin acetylation, which in turn enhances HSP90 binding to microtubules and facilitates nuclear localization of viral capsid protein [157]. Notably, this effect is completely opposite from that on NF-AT nuclear localization [150], indicating that tubulin acetylation regulates nuclear import in a context-dependent manner.…”
Section: Tubulin Acetylation In Immune and Viral Responsesmentioning
confidence: 99%
“…Some viruses induce significant acetylation of α-tubulin to stabilize the microtubule cytoskeleton for their intracellular transport by regulating HDAC6, including circovirus, herpes simplex°virus, and influenza A virus (Husain and Harrod, 2011; Zhong et al, 2014; Cao et al, 2015). Recently, HDAC6 has also been reported to be involved in the replication of certain viruses.…”
Section: Discussionmentioning
confidence: 99%
“…HDAC6 exerts its anti-IAV function by negatively regulating the trafficking of viral components via Actub to the host cell plasma membrane [22]. Other studies have shown that herpes simplex virus type 1 (HSV-1), human herpes virus 8 (HHV-8) and adenoviruses enhance microtubule acetylation to facilitate viral proliferation [4244]. Therefore, we considered that elevated Actub levels might be beneficial for viral proliferation.…”
Section: Discussionmentioning
confidence: 99%